2008
DOI: 10.1158/1078-0432.ccr-08-0234
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Mesenchymal Transition in Cervical Cancer: Correlation with Tumor Progression, Epidermal Growth Factor Receptor Overexpression, and Snail Up-Regulation

Abstract: Purpose: Acquisition of epithelial-mesenchymal transition (EMT) by primary carcinoma cells is associated with disrupted epithelial integrity, local invasion, and ultimately metastasis. Little is known about the existence and function of EMT in cervical cancer. This study aims to investigate the regulation of EMT in cervical squamous cell carcinoma. Experimental Design: We investigated the molecular events of EMT in surgical specimens, which present the progression of cervical carcinoma.Two cervical cancer cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
199
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(220 citation statements)
references
References 25 publications
18
199
3
Order By: Relevance
“…More important, we show that inactivation of Akt largely eliminates these EGF-mediated signaling events, suggesting that Akt is a central player in EGFRdirected cell migration. Similar observations have been recently reported in cervical cancer cells (Lee et al, 2008). In addition, we found that knockdown of endogenous Snail in prostate cancer cells significantly interrupts EGF-induced E-cadherin loss, EMT and motility.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…More important, we show that inactivation of Akt largely eliminates these EGF-mediated signaling events, suggesting that Akt is a central player in EGFRdirected cell migration. Similar observations have been recently reported in cervical cancer cells (Lee et al, 2008). In addition, we found that knockdown of endogenous Snail in prostate cancer cells significantly interrupts EGF-induced E-cadherin loss, EMT and motility.…”
Section: Discussionsupporting
confidence: 92%
“…Studies within carcinoma cell lines from disparate epithelial tissues have supplied evidence for several different signaling pathways (b-catenin-TCF/LEF-1, ERK, STAT3), as well as alternate repressors of E-cadherin transcription (Twist, Slug) involved in activation of EMT (Conacci-Sorrell et al, 2003;Lu et al, 2003;Lo et al, 2007), reflective of the fact that cancer cells can use completely distinct pathways under diverse biological contexts. Our work in prostate cancer cells, in addition to the study in cervical cancer cells (Lee et al, 2008), adds yet another mechanistic pathway by which carcinoma cells undergo EMT, specifically an EGF/EGFR-mediated EMT pathway through Akt inhibition of GSK3b, followed by stabilization of Snail and downregulation of E-cadherin (EGFR-Akt-GSK3b-Snail-E-cadherin-EMT). Interestingly, we observed that inhibition of ERK signaling rather boosts EGF-induced Akt activation, subsequently enhancing cell motility ( Figure 5 and Supplementary Figure 4).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…(20) In EMT-type cells, the reduction of the epithelial marker ECD occurs in parallel with the induction of the mesenchymal marker VIM. (21) Epithelial-mesenchymal transition occurs during cancer progression and enhances invasion and metastasis. (20) The present study aimed to clarify the relationship between morphogenesis, EMT, and growth factors in GBC cells.…”
mentioning
confidence: 99%
“…EMT markers have been associated with greater tumor invasion and progression in women with CC 31. In particular, HPV E6 oncoprotein expression induces characteristic changes in EMT 32.…”
Section: Discussionmentioning
confidence: 99%